2016
DOI: 10.1051/0004-6361/201629311
|View full text |Cite
|
Sign up to set email alerts
|

Multi-wavelength observations of IGR J17544-2619 from quiescence to outburst

Abstract: In this paper we report on a long multi-wavelength observational campaign of the supergiant fast X-ray transient prototype IGR J17544-2619. A 150 ks-long observation was carried out simultaneously with XMM-Newton and NuSTAR, catching the source in an initial faint X-ray state and then undergoing a bright X-ray outburst lasting approximately 7 ks. We studied the spectral variability during outburst and quiescence by using a thermal and bulk Comptonization model that is typically adopted to describe the X-ray sp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
22
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 52 publications
(88 reference statements)
3
22
0
Order By: Relevance
“…In the case of the SFXT prototype IGR J17544-2619, large increases in the absorption column density were not detected during either the many outbursts observed with Swift /XRT (Romano et al 2008a(Romano et al , 2011a, XMM-Newton (Bozzo et al 2016a), and Suzaku (Rampy et al 2009), or during the fainter flares analyzed here. The spectral variability seems more related to changes in the power-law photon index and so to the emission mechanism intrinsic to the source (see the exhaustive discussion in Bozzo et al 2016b, and references therein), while the absorption column density does not change dramatically between quiescence and the very bright X-ray states (in 't Zand 2005).…”
Section: Classification Of Sfxt Flares and Outburstsmentioning
confidence: 51%
See 2 more Smart Citations
“…In the case of the SFXT prototype IGR J17544-2619, large increases in the absorption column density were not detected during either the many outbursts observed with Swift /XRT (Romano et al 2008a(Romano et al , 2011a, XMM-Newton (Bozzo et al 2016a), and Suzaku (Rampy et al 2009), or during the fainter flares analyzed here. The spectral variability seems more related to changes in the power-law photon index and so to the emission mechanism intrinsic to the source (see the exhaustive discussion in Bozzo et al 2016b, and references therein), while the absorption column density does not change dramatically between quiescence and the very bright X-ray states (in 't Zand 2005).…”
Section: Classification Of Sfxt Flares and Outburstsmentioning
confidence: 51%
“…In that occasion, an increase by a factor of ∼10 of the absorption column density in the direction of the source preceding the flare revealed that a massive and dense structure was rapidly approaching the NS, giving first rise to a large increase in flux (a factor of ∼1000) before obscuring the compact object and finally moving away from the observer line of sight. Bozzo et al (2016a) also fortuitously caught with XMM-Newton an episode of strongly enhanced X-ray activity from the SFXT IGR J17544-2619 that reached the typical luminosity of an X-ray outburst but displayed only a marginal increase in the local absorption column density (a factor of 2). Estimating the physical properties of the clumps in a reliable way from these observations have been proved complicated, due to our poor knowledge of the spin period and magnetic field of the NS in the SFXTs.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…THESEUS will provide excellent coverage of the outbursts of classical neutron star and black hole X-ray binaries, for example Supergiant Fast X-ray Transient variability reaches up to a factor of 10 6 (Romano et al, 2015), with peak luminosities up to 10 38 erg s −1 ; the hourtimescale flares from these OB plus (presumed) NS systems have frequently triggered the Swift-BAT. THESEUS can constrain the temperature and optical depth of the accretion column (Farinelli et al, 2012;Bozzo et al, 2016), and the origin of the bright flares possibly due to wind accretion onto a magnetar (Bozzo et al, 2008). THESEUS will detect and provide localization for several black-hole transients, monitoring daily their X-ray spectral evolution throughout their full outburst.…”
Section: Supernovaementioning
confidence: 99%
“…In this case the source is the SFXT prototype IGR J17544-2619 and the lightcurve is obtained from the longest continuous observational campaign performed in X-rays on one of these sources (ID. 0744600101; (Bozzo et al, 2016)). The more extreme variability compared to the classical SgXB can be immediately seen by comparing this lightcurve with that on the top panel.…”
Section: Stellar Wind Parameters From X-ray Observations Of Classicalmentioning
confidence: 99%